Systematic review and meta-analysis of the impact of infectious diseases consultation on outcomes of Staphylococcus aureus bacteremia in children - Haripriya Santhanam; Nirmal Muthukumarasamy; Mariana Kim Hsieh; Karen Brust; Melanie Wellington; Toshio Naito; Riley J. Samuelson; Alexandre R. Marra; Takaaki Kobayashi (Cambridge University Press, 2024)
For adult patients with Staphylococcus aureus bacteremia (SAB), Infectious Diseases consultation (IDC) significantly lowers mortality and recurrence rate. Our systematic review and meta-analysis demonstrate that IDC is also associated with significantly lower mortality in children with SAB. Analysis of the impact of IDC on pediatric recurrence rates revealed moderate heterogeneity.